2023
DOI: 10.1088/2515-7620/acefb3
|View full text |Cite
|
Sign up to set email alerts
|

Emissions trading system: bridging the gap between environmental targets and fair competition

Massimo Beccarello,
Giacomo Di Foggia

Abstract: The effectiveness of the European Emissions Trading System in supporting a level playing field while reducing total emissions is tested. While data show a robust impact on the environment as a steady decrease in carbon emissions is observed, it is reported that its ability to internalize emission costs may improve to better address the import of extra European generated emissions that negatively impact the economy when not properly accounted for. Analyzing data in six European countries between 2016 and 2020, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…This implies investing in clean technologies and encouraging more energy-efficient production practices [38]. In addition, the observed negative correlation between the relative sector size and the gap indicated that the sectors with higher emissions were effectively monitored [13]. There may be value in intensifying monitoring and regulatory efforts in industries with fewer emissions, which may escape effective tracking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This implies investing in clean technologies and encouraging more energy-efficient production practices [38]. In addition, the observed negative correlation between the relative sector size and the gap indicated that the sectors with higher emissions were effectively monitored [13]. There may be value in intensifying monitoring and regulatory efforts in industries with fewer emissions, which may escape effective tracking.…”
Section: Discussionmentioning
confidence: 99%
“…The variables used to develop the model were selected among those related to climate issues available in the EU dataset and are as follows: gap measured the difference between Ratio between free allowances and verified emissions. Source: Our own elaboration on the ETS data viewer and [13], and all industrial sectors, except combustions.…”
Section: Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…With the aim of contextualizing the expected investments in technologies for the green transition, this section reviews the main drivers of decarbonization in light of recent European climate policies established in the Green Deal, including the fit for 55 package that aims to reduce net GHG emissions by at least 55% by 2030 and set ambitious decarbonization targets to be achieved by 2050 [1]. Existing policies and legislation are being updated to accommodate this transition [18], along with the design of efficient carbon markets that concurred in gradually reducing carbon emissions while preserving fair competition [19]. Indeed, finding an equilibrium between environmental and economic sustainability is challenging.…”
Section: Introductionmentioning
confidence: 99%